2022
DOI: 10.15252/embr.202152990
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase 1 knockdown induces age‐related β‐cell dysfunction and glucose intolerance in mice

Abstract: Tight control of glycemia is a major treatment goal for type 2 diabetes mellitus (T2DM). Clinical studies indicated that factors other than poor glycemic control may be important in fostering T2DM progression. Increased levels of methylglyoxal (MGO) associate with complications development, but its role in the early steps of T2DM pathogenesis has not been defined. Here, we show that MGO accumulation induces an age-dependent impairment of glucose tolerance and glucose-stimulated insulin secretion in mice knockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Indeed, increased levels of dicarbonyls, observed in diabetes and aging, induce cellular senescence in ECs [ 11 ]. We recently verified the crucial role of a premature β-cell senescent phenotype in vivo in the alteration of glucose homeostasis induced by MGO accumulation [ 12 ]. Senescent ADSCs lose their angiogenic potential and the transplantation of them causes dysfunction in mice [ 22 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, increased levels of dicarbonyls, observed in diabetes and aging, induce cellular senescence in ECs [ 11 ]. We recently verified the crucial role of a premature β-cell senescent phenotype in vivo in the alteration of glucose homeostasis induced by MGO accumulation [ 12 ]. Senescent ADSCs lose their angiogenic potential and the transplantation of them causes dysfunction in mice [ 22 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…MGO induces cellular dysfunction through several mechanisms including cellular senescence [ 11 ]. We have recently demonstrated that MGO accumulation induces a β-cell senescence-associated pro-inflammatory phenotype that contributes to the establishment of an early phenotype typical of type 2 diabetes mellitus (T2DM) progression [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While acetylation and oxidation do not affect GLO I activity, glutathione acylation emerges as a potent inhibitor [16]. GLO I dons the attire of phosphorylation on Thr107, and TNFα orchestrates its modulation through PKA-induced phosphorylation, resulting in a dramatic ballet of caspase-dependent cell demise accompanied by a dazzling display of reactive oxygen species (ROS) [4,19,20]. These ROS spectacularly inhibit GLO I, ushering in the intracellular buildup of pro-apoptotic AGEs, such as argpyrimidine, and kickstarting a mitochondrialdependent apoptotic pathway [21][22][23][24].…”
Section: Glyoxalase Imentioning
confidence: 99%